Good governance in the context of prevailing wide-spread corruption in public life - Experience-sharing and lessons (Note) - Somiah, C.G. (2003)
Many among veteran civil servants of the country are concerned by the falling standards of governance and increasing instances of corruption. The author of the note still sees a silver lining to the gloom and pins his hope on the young generation of administrators. A handful of tips based on the long experience in administration should be useful for the new entrants to the civil services. - Reproduced.
Keywords: Note; Good governance